Răspunsuri

2014-09-02T20:46:06+03:00
A + b + c = 256
b = a - 37
b = c - 87, din aceste 2 ec, rezulta ca
a - 37 = c - 87
a - c = - 87 + 37
a - c = - 50
inlocuim pe  b = a - 37 in prima ecuatie
a + a - 37 + c = 256
2a + c = 256 + 37
2a + c = 293 si
a    - c = - 50, le adunam 
3a   /   = 243
a = 243/3
a = 81
b = 81 - 37
b = 44
81 + 44 + c = 256
c = 256 - 81 - 44
c = 131
6 4 6
Cel mai inteligent răspuns!
2014-09-02T21:17:04+03:00
A+b+c=256
a=b+37
c=b-87
Înlocuind rezultă
b+37+b+b-87=256
3b-50=256
3b=306
b=306\3
b=102
a=102+37
a=139
c=102-87
c=15

3 5 3